Analisis Hukum dan Kriminologi terhadap Fenomena Penyalahgunaan Zat Dextromethorphan dalam Obat Batuk di Manado - Sri Yulianty Masoara (Universitas Batanghari Jambi, 2023)
The phenomenon of dextromethorphan (dextro) abuse is rife in Indonesia. Several cases indicate the occurrence of this abuse. As an example of the case of dextro abuse that occurred in Manado, North Sulawesi, a woman with the initials IR (25), was found dead in a hotel room in Wanea sub-district, Saturday (09/05/2020) after consuming liquid cough medicine containing dextro. Dextro The phenomenon of abuse of dextromethorphan dextro) is rife in Indonesia. Several cases indicate the occurrence of this abuse. On Saturday (5/9/2020), a woman with the initials IR (25) was found dead in a hotel in Wanea District, Manado, North Sulawesi. His death was cited as an example of a case involving dextro abuse. Cough drops in liquid form containing dextrose should be taken indoors. Coughs are actually treated with dextroactive drugs, and the action of these substances is to suppress dry coughs. This is done in the medical field. This dextrorotatory chemical can be found in a variety of cough suppressants, including Komix DT, Vicks Formula 44 DT, Siladex Antitussive, and Bisolvon Antitussive. An empirical justice strategy was used to conduct this research. The data needed to compile this article are both quantitative and qualitative, and the data is based on primary and secondary sources of information. In general, the purpose of making drugs and the function of the drug itself is to treat various diseases that can affect humans and animals. However, it is often misunderstood by some for inappropriate purposes, such as dextromethorphan. If explored more deeply, dextromethazepam is included in the Class III Narcotics group in the Appendix to Law Number 35 of 2009 concerning Narcotics (Narcotics Law). It was given the name dextropropoxyphene and occupies the second position in the Class III group of narcotics. To achieve this goal, the existence of a legal rule that guarantees all of this, or in other words, the fact that humans are governed by law, is one of the tools or instruments that will be used to achieve this goal. However, in its implementation it is also necessary to pay attention to elements such as legal certainty where in this case the law must be made in written form, besides that it must also pay attention to the benefits in applying the law and finally what is arguably the most important, namely the law must pay attention to justice in its application.